Independent multitone jamming of FH - Zhan Yu
We derive exact expressions of the symbol error rate (SER) performance of orthogonal, frequency-hopped, noncoherent M-ary frequency-shift-keying (FH/MFSK) receivers in the presence of independent multitone jamming (MTJ), as well as thermal and other wideband Gaussian noises. Both the signal tones and the multiple jamming tones are affected independently by Rician fading. Both the slow-hopping and fast-hopping systems are considered. In our derivation, we exploit the fact that the multipath components of the signal and jamming tones can be combined with the other Gaussian noises to form a single Gaussian process. Using this technique, we are able to obtain compact exact SER expressions which can be computed efficiently. From the computation results we provide physical explanations on the effects of several system parameters, such as jamming fraction, fading conditions and number of hops per symbol, on the SER performance of slow and fast FH/MFSK systems under independent MTJ
Keywords: FH/MFSK receivers; Gaussian process; Rician channels; Rician fading; SER performance; Exact expressions; Fading conditions; Fast FH/MFSK systems; Fast-hopping systems; Hops per symbol; Independent multitone jamming; Jamming fraction; Multipath signal components; Noncoherent M-ary frequency-shift-keying.; Orthogonal frequency-hopped receivers; Signal tones; Slow FH/MFSK systems; Slow-hopping systems; Symbol error rate performance; System parameters; Thermal noise; Wideband Gaussian noise